Crystalline Silicon Solar Cells with Thin Silicon Passivation Film Deposited prior to Phosphorous Diffusion - Ching-Tao Li; Fangchi Hsieh; Shi Yan; Cuifeng Wan; Yakun Liu; Jing Chen; Likarn Wang (International Journal of Photoenergy)
We demonstrate the performance improvement of p-type single-crystalline silicon (sc-Si) solar cells resulting from front surface passivation by a thin amorphous silicon (a-Si) film deposited prior to phosphorus diffusion. The conversion efficiency was improved for the sample with an a-Si film of ~5 nm thickness deposited on the front surface prior to high-temperature phosphorus diffusion, with respect to the samples with an a-Si film deposited on the front surface after phosphorus diffusion. The improvement in conversion efficiency is 0.4% absolute with respect to a-Si film passivated cells, that is, the cells with an a-Si film deposited on the front surface after phosphorus diffusion. The new technique provided a 0.5% improvement in conversion efficiency compared to the cells without a-Si passivation. Such performance improvements result from reduced surface recombination as well as lowered contact resistance, the latter of which induces a high fill factor of the solar cell.